Central bank digital currency and monetary policy implementation - Enea Caccia; Jens Tapking; Thomas Vlassopoulos (European Central Bank (ECB), 2024)
This paper discusses the impact that a retail central bank digital currency (CBDC) could have on the implementation of monetary policy. Monetary policy implementation could be affected if the introduction of the retail CBDC changes the volume of commercial bank deposits held by customers, which would, in turn, affect central bank reserves. While it is often assumed that customer deposits would decrease if a CBDC was introduced, we provide arguments why this is by no means clear cut and deposits could even increase. If bank deposits do decrease, banks would need to draw on, and therefore reduce, their central bank reserve holdings. Moreover, uncertainty as to the timing and extent of any conversions of deposits into CBDC might prompt banks to scale up their demand for central bank reserves in order to hold larger precautionary buffers. Consequently, central banks might need to adjust their reserve supply and other features of their monetary policy implementation, depending, for example, on whether they use a floor or a corridor system for monetary policy implementation. In the specific case of the digital euro, the features already envisaged for its design would make it possible to minimise the risk of negative consequences for monetary policy implementation.
Keywords: E41; E42; E43; E52; E58; G21; 330; Monetary policy implementation; central bank digital currency; central bank reserves